1) √(1-x) больше x+1 2) √(3x-2) больше х-2 3) √(2x+1)≤x+1
1) √(1-x)>x+1
2) √(3x-2)>х-2
3) √(2x+1)≤x+1
Ответ(ы) на вопрос:
Гость
1
1){1-x≥0⇒x≤1
{x+1≥0⇒x≥-1
{1-x>x²+2x+1⇒x²+3x<0⇒x(x+3)<0⇒-3x²-4x+4⇒x²-7x+6<0⇒1
Гость
1) √(1-x) > x+1 ;
эквивалентно совокупности двух систем неравенств :
a) { x+1< 0 ; 1 -x ≥ 0⇔ { x< -1 ; x ≤ 1 ⇒ x < -1 иначе : x∈ ( -∞ ; -1) .
или
b) {x+1 ≥0 ; 1-x > (x+1)². ⇔{ x≥ -1 ; (x+3)x <0 .⇔ { x≥ -1; -3< x <0. ⇒ x∈ [-1 ; 0).
значит : x∈ ( -∞ ; -1) ∪ [ -1 ;0) ⇔ x ∈ ( -∞ ; 0).
ответ : x∈ ( -∞ ;0 ) .
----
2) √(3x -2) > x - 2 ;
a) { x-2< 0 ; 3x -2 ≥ 0⇔ { x< 2 ; x ≥ 2/3 ⇒ x∈ [ 2/3 ;2) .
или
b) {x-2 ≥0 ; 3x -2 > (x-2)². ⇔
{ x≥2 ; x²- 7x +6 < 0 .⇔ { x≥ 2 ; (x-1)(x-6) < 0 ⇔ { x≥ 2 ; 1 < x <6⇒ x∈ [ 2 ;6) .
значит : x∈ [2/3 ;2) ∪ [ 2 ;6 ) ⇔ x ∈ [2/3 ; 6).
ответ : x ∈ [2/3 ; 6).
----
3) √(2x +1) ≤ x+1 ;
a) x +1 < 0 ⇒нет решения .
b) { x+1 ≥0 ; 0 ≤ 2x +1 ≤ (x+1)² .⇔{ x ≥ -1 ; x ≥ - 1/2 ; 2x +1 ≤ x²+2x +1 .⇔
{ x ≥ -1 ; x ≥ - 1/2 ; x² ≥ 0 ⇒ x ∈ [ -1/2 ; ∞) .
ответ : x ∈ [ -1/2 ; ∞) .
Не нашли ответ?
Похожие вопросы